Effect Of Arbutin Peel From Pyrus Communis On Cell Line (Journal of the College of Basic Education, 2024)
Arbutin (P-Hydroxyphenyl-Β-D-Glucopyranoside) Possesses Beneficial Extracted From Plant Pyrus Communis Functions Including Anti-Tumor Activities. Due To The Important Role Of Anti Tumor And Apoptosis In The Successful Treatment Of Cancer, Is Essential. The Purpose Of The Current Study Was To Evaluate The Effect Of Arbutin On Cell Line Hepg2 ,MCSF7 And MEF Cellline . Materials And Methods In This Experimental Study, Effect Arbutin And Extracted From Pyrus Communis In Hepg2 ,MCSF7 And MEF Cell Lines Were Pre-Treated With Arbutin (6.12 ,12.5, 25,50, And 100 Μm). After 24 Hours, T-BHP (30 And 35 Μm) Was Added To The Cells. Viability Was Measured (At 24) Using MTT Assay (3-[4,5-Dimethylthiazol-2-Yl]-2,5 Diphenyl Tetrazolium Bromide). Results: Arbutin Treatment To Cell Line Assay Including Effect Of Extract On Growth Of Tumor Cell Lines Hepg2, MCF7 And MEF Normal Cell Line Was Done By Using Cytotoxic Assay. The Findings Demonstrated That The Cytotoxicity Of The Extract Varied Depending On Cell Type And Concentration In Different Cell Lines. With Higher Extract Concentrations, Tumor Cell Line Inhibition Activity Increased. The Higher Inhibition Rate In Hepg2 Cell Line Was 92.01 % And 79.87 At The Concentration 100 µg\Ml While For MCF7 The Highest Inhibition Rate Was 62.12% And 59.87in Concentration 100 µg\Ml The Highest Inhibition Rate For MEF Cell Line Was 59.17 % And 42.81 In 100µ G\MlConclusion: Arbutin As A Potential Functional And Extracted Has Strong Ability To Inhibitory Effect On The Growth Of Cell Line And Decreased Effect In Normal Cell Line .